PERAN KELOMPOK TANI DEWASA LEMAH DUHUR DALAM PEMBERDAYAAN MASYARAKAT UNTUK PENGEMBANGAN LINGKUNGAN MELALUI KAMPUNG AGRO EDUWISATA ORGANIK CIHARASHAS (STUDI KASUS KELURAHAN MULYAHARJA, KECAMATAN BOGOR SELATAN, KOTA BOGOR) - Nada Nabilah; Muhtadi Muhtadi (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2021)
This study discusses the role of the Lemah Duhur Adult Farmer Group in community empowerment for environmental development through the Ciharashas Organic Agro Edu-Tourism Village. The theory used by researchers is the theory of the role of community workers, community empowerment, agro-tourism, organic agriculture, the environment, sustainable development, and the Logical Framework Approach. In this study, researchers wanted to see the role of the Lemah Duhur Adult Farmer Group, the results of their community empowerment, the supporting and inhibiting factors in carrying out community empowerment, and their relation to environmental development.The research method used by researchers is qualitative research. Then, the data collection techniques used were observation, interviews, and document study. Researchers conducted in-depth interviews to obtain a comprehensive understanding and were supported by field observations and documents obtained. Regarding the results of the research, the Lemah Duhur Adult Farmer Group has an important role in community empowerment through the Ciharashas Organic Agro Edu-Tourism Village in Mulyaharja Village, South Bogor District. Based on its implementation, the Lemah Duhur Duhur Adult Farmer Group plays a role as facilitative roles, educational roles, representational roles, dan technical roles. The results of community empowerment carried out bythe Lemah Duhur Adult Farmer Group have met the sustainability requirements, renewability, interdependence, adaptability, and institutional commitment.